Awareness and practices regarding climate change and its effects on health, in an urban community: a cross sectional study - Gopinath, Ishwar; Arulmozhi, P.; Murugan, S. Arun (International Journal Of Community Medicine And Public Health, 2023)
Background: Aim was to assess the level of awareness and practices related to climate change and its effects on health among urban population in metropolitan city. To recommend awareness programs regarding climate change and its health hazards for urban population based on results. Methods: Community based cross sectional study was conducted among 180 adults from January 2022 to March 2022. The data was entered in MS Excel and was analyzed by using SPSS-16 software. Results: The awareness about climate change was 63%. 76% of the respondents did not agree that climate change is related to extreme weather phenomenon. All the participants believed that climate change affects health, but none of them were aware that it is causing increased incidence of cancer. 73% of the participants always adopted climate friendly alternatives to using own motor vehicles. None of the participants practiced garbage segregation. Only 19% always used climate friendly alternatives to plastic bags. 74% respondents were unable to give concrete solutions to control climate change. 14% participants suggested planting more trees, 10% called for control of industrialization and population explosion. 66% obtained their information from newspapers. None of them viewed scientific journals. There was no significant association between educational status and awareness of climate change. Conclusions: The population is moderately aware of climate change. They are not well aware of its long-term impacts on health. There is an urgent need for them to be well informed with verified sources of information. Appropriate campaigns must be initiated.